Microbial analysis of endodontic infections in teeth with post-treatment apical periodontitis before and after medication - Erşahan, Şeyda; Erdem Hepşenoğlu, Yelda (Wiley, 2023)
This study aimed to determine the intraradicular microbiota of previously root canal-treated teeth with apical periodontitis and to investigate the antibacterial effectiveness of different intracanal medicaments. Sixteen patients with post-treatment apical periodontitis were allocated into two groups according to the intracanal medicament used: calcium hydroxide (CH) and 2% chlorhexidine gluconate gel (CHX) group. Total bacterial loads, as well as the amount of Enterococcus faecalis (E. faecalis) were determined before (S1) and after (S2) chemomechanical preparation and finally, after intracanal medication (S3) by means of ddPCR. The unpaired t test was used to compare parametric. S3-total bacteria copy number of the CH group was lower than the CHX group (p < 0.05). There was no statistical difference between the CHX- and the CH groups in terms of E.faecalis copy number (p > 0.05). But in terms of total bacteria, CH is better than CHX. Consequently, CH can be used to optimise the antibacterial efficiency of chemomechanical preparation in previously root canal-treated teeth with apical periodontitis.
Keywords: Chemomechanical Preparation; Droplet Digital; Enterococcus Faecalis; Intracanal Medicaments; Microbiology; Post-Treatment Apical Periodontitis; Total Bacterial Load